Determination of Critical Micelle Concentration of Sodium Dodecyl Sulfate in Distilled Water at 298.15K by Surface Tension Measurements - Yadav, Chandradip Kumar (Cognition, 2023)
Surfactants are chemicals that adsorb to the interface between a solution and another phase (gases or solids) and self-assemble molecular clusters known as micelles in a solution (water or oil phase). Measurements of the surface tension of sodium dodecyl sulfate (SDS) in distilled water at 298.15K are reported. The increase of concentration of sodium dodecyl sulfate (SDS) in distilled water then decreased in surface tension at 298.15K. Critical micelle concentration (CMC) decreased with a decrease in surface tension. The graphs of surface tension versus concentration were made to determine the CMC of the solution.